Colorimetric detection of residual hydrogen peroxide in soaked food based on Au@Ag nanorods. Issue 5 (22nd January 2018) - Chen, Qingai; Lin, Tianran; Huang, Jianli; Chen, Yi; Guo, Liangqia; Fu, Fengfu
Abstract : A simple and selective colorimetric method for H2 O2 detection in soaked food samples was developed using Au@Ag nanorods (Au@Ag NRs) as the signal conducter. Abstract : A simple and selective colorimetric method for H2 O2 detection in soaked food samples was developed using Au@Ag nanorods (Au@Ag NRs) as the signal conducter. In the presence of H2 O2, silver atoms on the surface of Au@Ag NRs are oxidized to silver ions, thereby resulting in the red-shift of the longitudinal surface plasmon resonance peak of Au@Ag NRs accompanied by a sharp-contrast multicolor change. The linear range for the detection of H2 O2 was from 0 to 100 μmol L −1 with a limit of detection of 3.2 μmol L −1 . Compared with the commercialized test strip, the proposed colorimetric sensor showed a much higher color resolution by the naked eyes.